2017
DOI: 10.3389/fncel.2017.00360
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Modeling Abnormal Neuronal Function in Schizophrenia Using Human Induced Pluripotent Stem Cells

Abstract: Excitatory dopaminergic neurons, inhibitory GABAergic neurons, microglia, and oligodendrocytes have all been implicated in schizophrenia (SZ) network pathology. Still, SZ has been a difficult disorder to study, not only because of the limitations of animal models in capturing the complexity of the human mind, but also because it is greatly polygenic, with high rates of variability across the population. The advent of patient-derived pluripotent stem cells and induced neural and glial cultures has brought hope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…The pioneer work of Brennand et al (2011) first characterized hiPSC-derived neurons from SZ patients and revealed decreased neuronal connectivity, decreased neurites, and decreased levels of post-synaptic protein PSD95 [94]. Subsequent studies focused on specific neuronal subtypes, such as pyramidal cortical interneurons and dentate gyrus granule neurons, and a series of studies revealed cell-autonomous neuronal disturbances in SZ [92,95]. Although pioneer studies confirmed postmortem findings and revealed additional aspects of the molecular mechanisms of SZ, hiPSC-based disease modeling has several limitations.…”
Section: Patient-derived Neurobiological Test Systems Indicate Oligodmentioning
confidence: 99%
See 1 more Smart Citation
“…The pioneer work of Brennand et al (2011) first characterized hiPSC-derived neurons from SZ patients and revealed decreased neuronal connectivity, decreased neurites, and decreased levels of post-synaptic protein PSD95 [94]. Subsequent studies focused on specific neuronal subtypes, such as pyramidal cortical interneurons and dentate gyrus granule neurons, and a series of studies revealed cell-autonomous neuronal disturbances in SZ [92,95]. Although pioneer studies confirmed postmortem findings and revealed additional aspects of the molecular mechanisms of SZ, hiPSC-based disease modeling has several limitations.…”
Section: Patient-derived Neurobiological Test Systems Indicate Oligodmentioning
confidence: 99%
“…Nevertheless, several conceptual limitations will remain, at least in the medium term. Examples of such conceptual limitations are as follows: (1) hiPSC-based systems cannot fully mimic the human gene x real world environment interactions that are part of the etiology of SZ [96], although aspects of known environmental risk factors (e.g., infection, stress, inflammation) can be modeled [95]; (2) hiPSC-based models are more powerful models of genetic risk for SZ than of SZ as a disease entity; (3) hiPSC models do not mimic network macro connectivity, which is assumed to be disturbed in SZ [97]; and, (4) long-lasting processes, such as aging and maturation over many years, are disturbed in SZ [98] but are difficult to mimic in vitro.…”
Section: Patient-derived Neurobiological Test Systems Indicate Oligodmentioning
confidence: 99%
“… 148 Recent studies have focused more on specific neuronal subtypes, such as pyramidal cortical interneurons, cortical interneurons and dentate gyrus (DG) granule neurons; these studies are reviewed in detail elsewhere. 20 , 149 …”
Section: Recent Observations and Challenges Of Patient-specific Neuromentioning
confidence: 99%
“…Mutations of disrupted-in-schizophrenia 1 (DISC1) are known to be associated with major psychiatric disorders, such as schizophrenia, autism, bipolar disorder, and depression (Porteous et al, 2011 ; Narayan et al, 2013 ; Prytkova and Brennand, 2017 ). Although hundreds of DISC1-binding proteins have been identified, little is known about how DISC1 interacts with those proteins to affect human brain development (Porteous et al, 2011 ; Bradshaw and Porteous, 2012 ; Lipina and Roder, 2014 ).…”
Section: Modeling Neurological Diseases With Organoidsmentioning
confidence: 99%
“…As the PSCs show significant variability which depends on the cell lines, passages, and even the properties of colonies or cells within a colony, careful selection of cell lines, and methods for reprogramming into iPSCs and culturing the cells should be considered in designing new organoid protocols. Meanwhile, the organoid field will benefit from standardized protocols and shared methodologies across different laboratories (Lancaster and Knoblich, 2014b ; Kelava and Lancaster, 2016a , b ; Prytkova and Brennand, 2017 ) as more different organoid protocols will be developed and coexist to provide options for studies depending on the strength of a specific protocol and the questions to address.…”
Section: Limitations Challenges and Future Directionsmentioning
confidence: 99%